The Relationship of Personal Hygiene and Physical Environmental Conditions with Scabies Symptoms - Alga, Nur’aini; Noerjoedianto, Dwi; Fitri, Adelina; Guspianto, Guspianto; Eka Putri, Fitria (Rifa'Institute, 2023)
Introduction: Scabies is a contagious skin disease caused by the female tick Sarcoptes Scabiei Varieta Hominis which belongs to the Arachnida group. Scabies can occur in countries with tropical and subtropical climates Obective: The purpose of this study was to determine the relationship between personal hygiene and environmental conditions with scabies symptoms at Al-Mubarak Islamic Boarding School in Jambi City. Method: This study used an analytical observational method with a Cross Sectional approach, the sample in this study were 85 respondents using simple random sampling. Result and Discussion: The results of this study showed a significant relationship between skin and hand hygiene (p = 0.001), towel hygiene (p = 0.033) with scabies symptoms. There is no relationship between clothing hygiene (p = 0.109) with scabies symptoms. Proportion of physical environmental conditions (clean water facilities, ventilation, occupancy density, humidity) that do not meet requirements 100%. Conclusion: Variables associated with scabies symptoms are skin and hand hygiene, and towel hygiene. Variables that are not associated with scabies symptoms are clothing hygiene. It is recommended to the boarding school to add exhaust fans and also pay attention to the clean water facilities used and the students to maintain personal hygiene such as routine bathing 2x a day, drying clothes and towels in the sun